Back to Keynes? - Frederick van der Ploeg (Center for Economic Studies and ifo Institute (CESifo), 2005)
After a brief review of classical, Keynesian, New Classical and New Keynesian theories of macroeconomic policy, we assess whether New Keynesian Economics captures the quintessential features stressed by J.M. Keynes. Particular attention is paid to Keynesian features omitted in New Keynesian workhorses such as the micro-founded Keynesian multiplier and the New Keynesian Phillips curve. These theories capture wage and price sluggishness and aggregate demand externalities by departing from a competitive framework and give a key role to expectations. The main deficiencies, however, are the inability to predict a pro-cyclical real wage in the face of demand shocks, the absence of inventories, credit constraints and bankruptcies in explaining the business cycle, and no effect of the nominal as well as the real interest rate on aggregate demand. Furthermore, they fail to allow for quantity rationing and to model unemployment as a catastrophic event. The macroeconomics based on the New Keynesian Phillips curve has quite a way to go before the quintessential Keynesian features are captured.
Keywords: E32; E63; E12; 330; Keynesian economics; New Keynesian Phillips curve; monopolistic competition; nominal wage rigidity; welfare; pro-cyclical real wage; inventories; Ungleichgewichtstheorie; Keynesianismus; Keynes John Maynard